The Impact of Ball Modification on Blind Students' Fundamental Football Technique Skills in Special Schools Tanjung Morawa 2024 - Panjaitan, Miktam Maulido; Debataraja, Cindi; Qomala, Febi; Adiguno, Muhammad Wisnu Almahdi; Riandra, Muhammad Nauval; Ginting, M. Zaka Gamara; Winata, Devi Catur (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives: This study aims to enhance the orientation and mobility skills of blind students at SLB Tanjung Morawa in 2024. Visual impairments significantly impact the ability of blind children to navigate their surroundings, leading to limitations in orientation and mobility. As an intervention, soccer was utilized as an active movement strategy to stimulate physical engagement and improve students’ spatial awareness, ultimately fostering greater independence in daily activities. Materials and Methods: This study employed a pre-experimental design with a one-group pre-test–post-test approach. The research subjects comprised six blind students with low vision characteristics, selected through purposive sampling based on specific criteria, including the degree of blindness and initial mobility competence. Data collection involved standardized orientation and mobility assessments conducted before and after the intervention. The soccer-based intervention was implemented through structured training sessions. Data were analyzed using non-parametric statistical methods, specifically the sign test, to evaluate the effectiveness of the intervention in enhancing students’ orientation and mobility skills. Results: The findings indicate a significant improvement in the orientation and mobility skills of blind students following the intervention. Pre-test scores ranged from 42 to 75, whereas post-test scores increased to a range of 67 to 90. Statistical analysis revealed a Z_H value of 2.05, exceeding the critical value at the 5% significance level (Z_H = +1.96), leading to the rejection of the null hypothesis. These results confirm that soccer-based intervention has a statistically significant positive impact on the orientation and mobility skills of blind students. Conclusions: The study concludes that soccer-based interventions significantly enhance the orientation and mobility abilities of blind students at SLB Tanjung Morawa. This method presents a viable alternative in special education curricula to improve movement and spatial navigation skills in visually impaired children. Future research should explore the long-term effects of soccer-based training on orientation and mobility development, as well as investigate the integration of other sports-based activities that may yield similar benefits. Additionally, expanding the study to include a larger and more diverse sample, incorporating various age groups and degrees of visual impairment, would provide more comprehensive insights into the efficacy of this approach.